Preparation and application of fluorescence dendritic macromolecular nanoparticles. Issue 197 (24th March 2019) - Feng, Hao-Hui; Pang, Long; Cong, Hai-Lin; Shen, You-Qing; Yu, Bing
Abstract: In recent years, carbon dots have shown great potential in biological imaging, drug delivery, and other fields. In this study, red fluorescent carbon dots with carboxyl functional groups on the surface were designed and prepared, and the fluorescence properties were studied. At the same time, the carbon dot was combined with dendritic macromolecules, and the aggregate particle size was about 25nm. This combination has good dispersion and stability in both water and methanol, and the DOX-loaded is about 6.72%. The small particle size makes it easy to enter the cells, so as to achieve the function of tumor treatment and cell imaging.